The Prevalence of Fentanyl in Drug-Related Deaths in Philadelphia 2004–2006 - Wong, Stella C.; Mundy, Lisa; Drake, Rebecca; Curtis, John A.; Wingert, William E. (Journal of medical toxicology, 2010)
Fentanyl is an increasingly common drug of abuse. The Philadelphia Medical Examiner's Office reported 252 drug-related deaths in Philadelphia that tested positive for fentanyl during the year 2006 in comparison to 22 and 19 in 2005 and 2004, respectively. We reviewed the data from 2004 to 2006 from the Philadelphia Medical Examiner's office. Key words such as fentanyl, drug, cocaine, ethanol, medic (medication), tox (intoxication), or poison were used as search words. In comparison to 2004 and 2005 data, there was a statistically significant increase in number of drug-related deaths (DRDs) and the percentage of DRDs that tested positive for fentanyl in 2006. We postulate that the increase in DRDs in 2006 may be related to increase use or abuse of fentanyl, lack of general public awareness that fentanyl is a potent opioid, inadequate dose of nalaxone and/or the surge of clandestinely manufactured fentanyl.